Benthic litter in the continental slope of the Gulf of Naples (central-western Mediterranean Sea) hosts limited fouling communities but facilitates molluscan spawning. (August 2022) - Rizzo, Lucia; Minichino, Riccardo; Virgili, Riccardo; Tanduo, Valentina; Osca, David; Manfredonia, Alessandro; Consoli, Pierpaolo; Colloca, Francesco; Crocetta, Fabio
Abstract: Seafloor pollution by benthic litter is an emerging phenomenon, although debris colonization by biota remains largely unexplored. We characterized the litter of the continental slope (~400–600 m) of the Gulf of Naples (Mediterranean) and investigated its fouling biota through integrative taxonomic approaches. Plastic pieces (82 %) with land-based origin (96 %) and limited sizes (10–20 cm) were the items most commonly encountered, suggesting a transfer to deep waters through floating and sinking. The majority of the items were not fouled, and the debris hosted an impoverished biota, leading to hypothesize that benthic litter supports wide communities only in shallow waters. Higher colonization rates were observed for gastropod and cephalopod eggs with no preference for materials and sizes, suggesting that even small pieces of soft plastic provide a spawning habitat for molluscs and affect species' connectivity in the deep-sea ecosystem. Holistic approaches are necessary to evaluate interactions between litter and biota. Highlights: The continental slope of the Gulf of Naples hosts a limited number of litter items. Plastic pieces with land-based origin and limited sizes were commonly encountered. The debris hosted an impoverished biota but supported molluscan spawning. Higher colonization rates were observed for gastropod and cephalopod eggs. Holistic approaches are necessary to evaluate interactions between litter and biota.